2012
DOI: 10.1002/ijc.27895
|View full text |Cite
|
Sign up to set email alerts
|

Predictions of survival up to 10 years after diagnosis for European women with breast cancer in 2000–2002

Abstract: Few studies have addressed longer‐term survival for breast cancer in European women. We have made predictions of 10‐year survival for European women diagnosed with breast cancer in 2000–2002. Data for 114,312 adult women (15–99 years) diagnosed with a first primary malignant cancer of the breast during 2000–2002 were collected in the EUROCARE‐4 study from 24 population‐based cancer registries in 14 European countries. We estimated relative survival at 1, 5, and 10 years after diagnosis for women who were alive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
46
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 31 publications
2
46
0
4
Order By: Relevance
“…In the study carried out by Allemani et al 17 , which was based on data records of the population, the relative ten-year survival among European women with breast cancer diagnosed between 2000 and 2002 showed values above 70% in most regions of the European continent. This percentage corroborates the results obtained by Soerjomataram et al 9 in a systematic review, in which they concluded that most Western developed countries had tenyear survival rates of around 70.0%.…”
Section: Discussionmentioning
confidence: 99%
“…In the study carried out by Allemani et al 17 , which was based on data records of the population, the relative ten-year survival among European women with breast cancer diagnosed between 2000 and 2002 showed values above 70% in most regions of the European continent. This percentage corroborates the results obtained by Soerjomataram et al 9 in a systematic review, in which they concluded that most Western developed countries had tenyear survival rates of around 70.0%.…”
Section: Discussionmentioning
confidence: 99%
“…31 Allemani et al noted relative survival estimates of 89% for patients with tumors confined to the breast and 62% for tumors with lymph node involvement. 32 Kim et al showed DFS of 113 months for patients with breast cancer with no lymph node involvement and 84 months for those who presented lymph node metastases. 33 Adjuvant hormone therapy with tamoxifen was responsible for a reduction in the risk of recurrence of 41% and in the risk of death from breast cancer of 34% in women in a study by the Early Breast Cancer Trialists' Collaborative Group -EBCTCG.…”
Section: Discussionmentioning
confidence: 99%
“…Przyczyny utrzymującego się zróżnicowania przeżyć w krajach europejskich budzą wiele kontrowersji, głównie w środowiskach lekarskich i decydenckich, toteż podjęto dalsze szczególowe badania oparte na danych klinicznych typu High Resolution, które dostarczają kolejnych dowodów, że proporcja pacjentów we wczesnym stopniu zaawansowania choroby nowotworowej oraz dostępność leczenia uznanego za optymalne ma największe znaczenie w kształtowaniu wskaźników 5-letnich przeżyć w populacji [19][20][21]. Wiedza ta ma fundamentalne znaczenie dla określania potrzeb i budowania strategii walki z rakiem oraz w ocenie jej efektywności zdrowotnej.…”
Section: Dyskusjaunclassified
“…Wiedza ta ma fundamentalne znaczenie dla określania potrzeb i budowania strategii walki z rakiem oraz w ocenie jej efektywności zdrowotnej. [19,20,[22][23][24][25].…”
Section: Dyskusjaunclassified